2009
DOI: 10.1183/09031936.00140408
|View full text |Cite|
|
Sign up to set email alerts
|

Converting venous acid–base and oxygen status to arterial in patients with lung disease

Abstract: The aim of the present study was to evaluate a method for calculating arterial values of pH, carbon dioxide tension (PCO 2 ) and oxygen tension (PO 2 ) from peripheral venous values.In total, 40 patients were studied. Arterial and peripheral venous blood were sampled at a department of respiratory diseases. Arterial values were calculated from venous, and measured and calculated values of arterial pH, PCO 2 and PO 2 were compared.Measured and calculated values of pH and PCO 2 correlated well, with the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 14 publications
4
35
0
2
Order By: Relevance
“…While there is consensus that such samples are unreliable for assessment of arterial P O 2 or P C O 2 , published studies have suggested that arterial and venous pH values are comparable [13,14,15,16,17]. Other studies have suggested that calculation of arterial acid-base and blood gas status can be made from measurements in the peripheral venous blood [20,21]. International guidelines for instituting non-invasive ventilation for patients with decompensated hypercapnic respiratory failure emphasize the acid-base status of a patient and the level of hypercapnia [22].…”
Section: Discussionmentioning
confidence: 99%
“…While there is consensus that such samples are unreliable for assessment of arterial P O 2 or P C O 2 , published studies have suggested that arterial and venous pH values are comparable [13,14,15,16,17]. Other studies have suggested that calculation of arterial acid-base and blood gas status can be made from measurements in the peripheral venous blood [20,21]. International guidelines for instituting non-invasive ventilation for patients with decompensated hypercapnic respiratory failure emphasize the acid-base status of a patient and the level of hypercapnia [22].…”
Section: Discussionmentioning
confidence: 99%
“…the 95% confidence interval. Errors in SpO 2 of ± 4% have been shown to give only small variation in calculated arterial pH and PCO 2 , these errors being fairly constant over the range of SpO 2 values [73].…”
Section: Sensitivity Of the Arty Methods To Assumptions And Measuremenmentioning
confidence: 91%
“…However, to understand whether these results reflect in a broader population, it was necessary to consider the sensitivity of calculations to measurement error and to the assumptions contained in the method. This sensitivity analysis was published in [72,73], and a summary follows.…”
Section: Sensitivity Of the Arty Methods To Assumptions And Measuremenmentioning
confidence: 99%
See 2 more Smart Citations